Modified location housing affordability index of low and middle income households in urban areas of Malaysia / Mohd Azren Hassan - Hassan, Mohd Azren (2020)
Globally, affordability is vital for the housing market. During the past few years, urban housing in Malaysia has inclined towards severely unaffordable prices. Housing affordability is to ensure that houses offered are affordable for every income groups, especially the low and middle-income households. If the location is included as part of housing affordability criteria, can house affordability be changed? When location is taken into consideration, would housing affordability be different between two income households? The definition together with the quantifying of housing affordability uses household income, and housing expenditure has disregarded transportation expenditure which forms a substantial amount of household expenditure. There are needs to include location as part of the housing affordability. Location of housing project will ultimately influence transportation expenditure. This research aims to determine the housing affordability by applying a simplified Location Housing Affordability Index on low and middle income households in urban areas of Klang Valley. The scope and limitation of the research are within low and middle income households' housing and transportation expenditure and relate the housing affordability to location. This research quantitatively examines three urban areas within the Klang Valley which are Kerinchi, Subang Bestari and Putra Heights, selected based on their distances to Kuala Lumpur as an employment centre. By combining both housing and transportation affordability, a simplified Location Housing Affordability equation has been created to indicate the housing affordability of 434 respondents from low and middle-income households answering a questionnaire survey from the selected urban areas. Using PLS-SEM, this research has identified a relationship between the household income, housing expenditure and transportation expenditure with Location Housing Affordability Index. The findings suggest that the overall location of the urban areas in Malaysia for the low and middleincome households is very unaffordable. In the same time, the finding also suggest that an urban area near (Kerinchi) to employment centre is deemed to be affordable, for intermediate (Subang Bestari) and further (Putra Height) from employment centre are very unaffordable. The recommendation is to propose a simplified equation of the Location Housing Affordability Index as a measuring tool to determine housing affordability in Malaysia. Furthermore, it recommends enhancing housing rental market close to employment centres in relation to location and transportation expenditure. Moreover, the impact of location on housing expenditure needs to be included in the calculation of affordable housing.